Teknologi Budidaya Kedelai yang Adaptif pada Gawangan Tanaman Karet Belum Menghasilkan - Siti Rosmanah; Miswarti Miswarti; Alfayanti Alfayanti; Tri Wahyuni; Taupik Rahman; Hertina Artanti; Herlena Bidi Astuti; Shannora Yuliasari; Yahumri Yahumri; Wawan Eka Putra (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Space between plant (Gawangan) of immature rubber plant is one of the potential locations for the development of soybean plants. This study aims to obtain recommendations for adaptive soybean cultivation technology packages for immature rubber plantations. The research was conducted in August-November 2018 on a three-year-old rubber plantation in Gardu Village, Armajaya District, North Bengkulu Regency, Bengkulu Province. The study was conducted using a randomized block design of 4 treatments which was repeated 5 times. The data collected included the components of growth and yield of soybeans as well as input and production costs for each technology package. The growth component and yield component data were analyzed using analysis of variance and if there was a difference, then Duncan Multiple Range (DMRT) was done. The feasibility of farming is calculated from the value of the cost of revenue (R/C ratio). The results showed that the treatment had a significant effect on the number of branches, empty pods, weight of filled pods, filled seeds, seed weight per plant. However, the treatment had no significant effect on plant height, filled pods, number of pods per plant, empty or damaged seeds, number of seeds per stem, percentage of empty or damaged seeds, 1000 grain weight of seeds. All technology packages are economically feasible to develop because they have an R/C ratio > 1.